Chukwuemeka Ike and his Craft: An Analysis of Didactic Elements in Selected Novels of an African Fictional Icon - Anyanwu , Patricia Ngozi (International Journal of Arts, Languages, Linguistics and Literary Studies, 2024)
Despite a massive intellectual effort lavished on theories of African development, with particular emphasis on sensitizing members of the society on the need for mental and moral re-orientation, to see if society can make desired developmental progress, there appears to be little or no success. To these efforts, social scientists have added the didactic elements in Chukwuemeka Vincent Ike’s fiction. Within here also is a massive effort geared towards positive transformation of society through consciousness raising. Through the technicalities of setting, voice, character and action, Chukwuemeka Vincent Ike engages his art in order to portray his perception of the numerous social, economic and political realities of his day. Amongst these realities as expressed in his eleven novels are issues of Nigerian Biafran war and its devastating effects, the challenge of irresponsible leadership and economic waste by the democratic leaders who inherited power at independence, the need for harmony in the family, the African conspiracy of silence on the issue of fatherless children in the society, his concern with the youth, the-neglected future leaders of the nation and many more. Ike presents these concerns as essential for attaining the much-desired developmental progress in Nigeria and Africa at large. Sadly, the ink in the pen of this erudite African fictional icon has faded with his departure for the great beyond. Certainly, his arrival in the abode of his ancestors will be heralded with much joy because of his indelible foot prints on the sands of time in African prose fiction. But their gain is certainly our loss! We will surely miss his peculiar approach to the art of storytelling, particularly his refraction of reality into fiction. We will miss his humor, subtle satire as well as the didactic elements embedded in his fictional creations, particularly his legacy of advocacy for family coherence and proper upbringing of the child. This paper therefore examines the life, legacy, and didactic elements encapsulated in notable works of one of Africa’s first-generation literary giants, His Royal Highness Professor Chukwuemeka Vincent Ike.